El durazno: variedades y sus nuevos aportes y desafíos en la gastronomía ecuatoriana - Dávila Rueda, Santiago Miguel (2016)
This paper bases its research on 3 different types of ecuadorian peach specifically in the highlands of Ecuador like yellow peach, white peach and abridor peach, the objectives are to publicize these varieties because I believe that gradually It is losing the consumption of these fruits, encourage consumption with the development of traditional recipes and products that can be dispensed in the local market. Recipes and products were produced at home with the implementation of simple culinary techniques, good ygiene practices and food handling. The results were quite flattering because we create various products that are not easily offer with new and delicious flavors. Our challenge now is to encourage consumption, do not lose the traditions of our ancestors, although production is not as great gradually encourage planting, the national government and support for small producers with low interest loans, training constant and productive incentives. UDLA from their classrooms, from their teachers, with teaching as a primary point of use and consumption of these products, with innovation to new techniques, new recipes, new products. We as Food and Beverage Technologists help to contribute equally with ecuadorian gastronomy from the area that we can, from the kitchens, from classrooms, from our homes.